(untitled) (Journal of Medical Device Technology, 2024)
Hydroxyapatite has become an important material for bone scaffold fabrication. Various method has been investigated in developing nano-hydroxyapatite that mimicking the native bone properties. Co-precipitation approach is the best synthesis method due to capability in producing hydroxyapatite with controlled size and morphology. However, to determine the parameters in producing good hydroxyapatite has become a challenge. Therefore, the aim of this study is to synthesis the nano-hydroxyapatite with right size and composition via co-precipitation method. In this study, calcium nitrate tetrahydrate and ammonium phosphate dibasic were mixed for 3 hours at pH11 before left ageing for 24 hours. The morphology of the hydroxyapatite nanoparticle was in rod-like look as observed by Transmission Electron Microscopy (TEM). The average diameter of the hydroxyapatite nanoparticle was 8.49 ± 0.36 nm, whereas the average length was 37.46 ± 1.86 nm. Energy Dispersive X-ray Spectroscopy (EDX) analysis yield the result of Ca/P ratio of 1.43 which is close to the stoichiometry of hydroxyapatite, 1.67. Produced nanoparticle confirmed co-precipitation method is the best choice in synthesizing nano size hydroxyapatite that suitable for bone tissue engineering application.